Lost in Information How Cyberchondria and Consumer Confusion Drive Purchase Avoidance in Gen Z Across Indonesia and Malaysia - Mohamad Rifqy Roosdhani; Muhammad Khoiruddin; Samsul Arifin; Nurul Komaryatin; Ali Ali; Nurul Huda (Universitas Islam Nahdlatul Ulama Jepara, 2026)
Objective: This study examines how information overload (IO) influences purchase avoidance (PA) among Generation Z consumers in Indonesia and Malaysia, focusing on the mediating roles of cyberchondria (CY) and consumer confusion (CC), and exploring gender differences in these effects. Gender-specific responses to IO in Gen Z remain underexplored in developing regions, despite their importance for digital marketing strategies. Research Design & Methods: This study employed a quantitative method using PLS-SEM, with data collected via questionnaires from 426 Gen Z respondents in Indonesia (192) and Malaysia (204) through accidental sampling. Findings: Information overload raises cyberchondria and confusion in both genders but does not directly impact purchase avoidance. Cyberchondria mediates the IO–PA link for all, while confusion mediates it only for females. Research Implications: Findings indicate that information overload affects Gen Z’s purchase avoidance mainly through psychological factors, with cyberchondria mediating for all and confusion influencing only females. Practical Implications: Marketers should simplify information and address health-related anxiety, particularly in female Gen Z, to reduce purchase avoidance. Social Implications: The study highlights psychological challenges, such as confusion and health anxiety that affect Gen Z’s well-being and decision-making in dense online information environments. Contribution & Value Added: This research shows information overload indirectly affects Gen Z’s purchase avoidance, with cyberchondria and confusion as key mediators and gender differences in the confusion pathway.